KONSEP TOLERANSI DALAM AL-QURAN DAN RELEVANSINYA BAGI KEHIDUPAN BERAGAMA YANG MODERAT - Salwa, Niam (IBTIKAR: Jurnal Studi Islam dan Sosial, 2026)
Tolerance from the Qur’anic perspective is not merely a passive attitude of respecting differences, but rather an active expression of faith inspired by empathy the capacity to understand, feel, and appreciate the experiences of others, including those of different religions or worldviews. This study is motivated by the growing influence of exclusive religious narratives in Indonesia that tend to separate faith from its social and emotional dimensions, thereby risking intolerance and social fragmentation. The research aims to uncover the concept of tolerance in the Qur’an as an integrated whole of faith and empathy, and to explore its relevance in fostering a moderate and inclusive religious life within Indonesia’s pluralistic society. Using a qualitative approach and library research methodology, the study analyzes relevant Qur’anic verses such as Q.S. Al-Hujurat: 13, Al-Kafirun, and Al-Ma’idah: 48 through contextual hermeneutics, while also drawing on the ideas of Indonesian Muslim thinkers (notably Nurcholish Madjid) and official Ministry of Religious Affairs documents on religious moderation. Findings indicate that the Qur’an frames tolerance within a universal humanistic framework: it not only guarantees freedom of religion but also demands an active commitment to justice, mutual recognition (ta‘araf), and the nurturing of social harmony. Empathy is thus shown to be the ethical foundation for interpreting and embodying these values. Authentic religious moderation, therefore, emerges when faith is expressed not only through ritual but also through openness of heart toward human diversity. These findings strengthen the theological basis for the narrative of Islam Rahmatan lil ‘alamin (Islam as a mercy to all creation) in Indonesia